1-G experimental study of the collapse effects on buried steel gas pipelines. (October 2022) - Liu, Peng; Huang, Weihe; Li, Yuxing; Sun, Mingyuan; Zhang, Yu; Fan, Jialin; Zhang, Yan
Abstract: Collapse disasters are commonly occurring geological disasters around buried gas pipelines and severely threaten the safety of pipeline operations. In this study, to investigate the soil deformation characteristics and mechanical response law of the pipeline under collapse, an experimental box (6 m × 1 m × 1.2 m) was built, and 1-G collapse experiments with different pipe diameters and burial depths were performed. The soil deformation laws, change in earth pressure around the pipeline, and mechanical response of the pipeline during the expansion of the collapse range were obtained by comparing and analysing the experimental results. Pipeline collapse disasters can be divided into two stages: before and after large-scale collapse disasters. The burial depth has an influence on pipeline collapse disasters mainly in a small-scale collapse range. As the collapse range increases, the influence of the burial depth on the strain distribution of the pipeline gradually decreases. However, an increase in pipe diameter can lead to a significant increase in the large-scale collapse range. Large-diameter pipelines bear greater strain than small-diameter pipelines after a large-scale collapse. This study provides data support for further research and serves as a valuable reference for pipeline safety evaluation in collapse disasters. Highlights: An experimental box was built and continuous collapse experiments were carried out. Soil deformation, earth pressure and mechanical response of pipeline were studied. The influence of buried depth on pipeline collapse disaster was studied. Effects of pipe diameter on pipeline collapse disaster were studied.